Manganese Toxicity on Manganese Accumulation and Mineral Composition of Tomato (Solanum lycopersicum L.) - Akinci, I.E.; Akinci, S.; Yilmaz, K. (Asian Journal of Chemistry, 2010)
A greenhouse pot culture experiment was conducted to determine the effects of increasing manganese dose (0, 50, 100 or 200 mg L-1 Mn) on growth, manganese accumulation and element changes in tomato (Solanum lycopersicum L. cv. Falcon) seedlings. Excess Mn as 100 and 200 mg Mn L-1 decreased all the growth parameters according to control plants. Manganese accumulation significantly increased in the parts of the seedlings with increasing amounts of Mn. A positive interaction was observed between 50 mg L-1 Mn and uptake of all elements except Zn content in root, shoots and leafs and Ca content in leaf of in seedlings and growth. Elevated Mn as 100 and 200 mg L-1 were commonly limited growth and uptake macro-micro elements by plant parts. Effects of Mn in low concentrations as 50 mg L-1 dose of Mn was stimulate but Mn in excess levels as 100 and 200 mg L-1 was limited for tomato seedlings characteristics.